Difficulties Reported by Informal Caregivers of the Elderly During the Covid19 Pandemic - Almeida Neto, Euritse Diana (2023)
Introduction: According to Hughes, Liu, and Baumbach, (2021), there was a negative impact on the health of informal caregivers during the COVID-19 pandemic. As a result of the SARS-CoV2 virus pandemic, which emerged in December 2019 in China, it was found that the difficulties reported by the informal caregivers were exacerbated. Objective: To map and examine the difficulties reported by the informal caregivers of the elderly during the COVID-19 pandemic. Methods: An integrative literature review was elaborated, in which the mnemonic Population, Concept and Context was used. The research was carried out through the EBSCOhost platform, to access CINAHL Complete and Psychology and Behavioral Sciences Collection databases, the platform Pubmed was used to access MEDLINE. Results: The profile of the caregivers was traced, these are mostly female, direct relatives of the person cared for, namely children and spouses. The average age ranges from 54 to 68 years old and in general, they have literacy. Conclusion: The difficulties were grouped into 4 major areas: health, social, financial and relational, which in turn are subdivided into 9 subthemes.